A new take on the assessment of first-year art projects - Westraadt, G. (South African Journal of Higher Education, 2017)
In a search for fresh forms of formative assessment that promotes student learning and encourage students to take responsibility for their own learning, a reflective study was conducted after two assessment instruments were applied in the evaluation of first-year B Ed students in Art Education. The first assessment was designed to assist students to overcome their apprehension about mark-making (drawing) and with the second, consideration was given to whether assessments prepared students for a lifetime of learning. Many first-year students entering their teacher training have not done any art since primary school. As part of the B Ed course they are required to produce a practical portfolio where they apply the art elements. For some students, this is a daunting task because they have very little confidence in their own creative ability. As a strategy to overcome their initial fear of drawing, a River of Life (Fisher & White 2014) exercise was introduced to set off their practical work. The theoretical component of the B Ed 1 course in Art Education comprises of a) the didactics of the subject and b) basic background knowledge of South African art and artists. A component of this work is assessed by means of a written test, but in the past the outcome was very poor. In an attempt to improve their lack of knowledge in this regard, instead of a written test, students were required to come to class with prepared notes and using that, had to design a flowchart as if in preparation for a slide show of a particular component of the work. Some examples of the end results of the River of Life drawings were analysed and will be discussed to establish whether it could be considered a reliable instrument to assess the ability of B Ed 1 students in the practical application of the elements of art. Results of the flowcharts as part of the theory assessment have been analysed to ascertain whether it has been a reliable assessment tool for this particular component of their course, enabling students to source and apply knowledge about art and artists of South Africa. Results of this research could suggest guidelines to forms of assessment other than the traditional, as reliable instruments in Art Education.